Effects of Tibetan medicine metacinnabar (β-HgS) combined with imipramine or sertraline on depression-like symptoms in mice - Qiao, Yajun; Li, Cen; Zhang, Ming; Zhang, Xingfang; Wei, Lixin; Cao, Keshen; Zhang, Xiaoyuan; Bi, Hongtao; Gao, Tingting (Frontiers in Pharmacology, 2022)
Depression is a common mood disorder that has exhibited an increased incidence rate worldwide, but the overall clinical efficacy of antidepressants remains unsatisfactory. In traditional Ayurveda and Tibetan medicines, β-HgS-containing medicines have been used to treat neurological diseases for thousands of years, and our previous study found that β-HgS ameliorated depression-like behaviors in chronic restraint stress (CRS)-treated or chronic unpredictable mild stress (CUMS)-treated mice. Hence, present study investigated the effects of β-HgS combined with the clinical first-line antidepressants, imipramine (IMI) and sertraline (SER), on depression-like symptoms in CRS- and CUMS-co-treated mice. Our results revealed that β-HgS promoted the antidepressant effect of SER on depression-like behavior in mice, and enhanced its effects on promoting glucocorticoid receptor (GR) expression and neuronal proliferation in key hippocampal subregions, as well as increasing interleukin 10 (IL-10) levels and decreasing malondialdehyde levels in the sera of stress-stimulated mice. As for IMI, β-HgS enhanced its effects on preventing atrophy and severe structural damage in the hippocampus, as well as in promoting hippocampal GR levels and neuronal proliferation and serum IL-10 and superoxide dismutase (SOD) levels. Additionally, combination therapy resulted in the increased diversity of important intestinal microbiota compared to that of monotherapy, which may help sustain the health of the digestive tract and reduce inflammation to further enhance the antidepressant effects of IMI and SER in mice.